HUBUNGAN BEBAN KERJA DENGAN KINERJA PELAPORAN DATA PELAYANAN KESEHATAN IBU DAN ANAK DI KOTA SEMARANG - Asti Dwi Noverina; Sutaip Sutaip; Nurizqi Salsa Ramdhani (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2021)
The implementation of the maternal and childh health program cannot be separated from recording and reporting as documentation and evaluation of all activities that have been carried out. The implementation of the KIA program starts from maternity huts, sub-health centers, private service facilities which are finally collected from monthly monitoring reports on maternal and child health areas. In fact, the Central Statistics Agency has not carried out data reporting properly, namely the Central Statistics Agency does not report maternal and childh health program service data, reports are not timely and reporting reports are incomplete. The purpose of this research is as an effort to improve puskesmas through planning, implementing, monitoring, controlling and assessing so that it can provide quality, relevant and valid information. Observational research using survey method with cross sectional approach. The independent variable studied is workload and the dependent variable is the performance of reporting data on maternal and childh health program services. The sampling technique was proportional random sampling at 35 Puskesmas to determine the number of samples in each strata/region and simple random sampling to determine the sample in each selected area. Data processing using the stages of editing, coding, entry, and tabulating. Analysis of the data used is univariate analysis with frequency and percentage distributions and bivariate analysis with statistical tests using Spearman's Rank Correlation test. Based on the results of statistical tests using Spearman's Rank Correlation, p value = 0.001 (p 0.05). This shows that there is a significant relationship between workload and reporting performance of maternal and childh health program a service data. The Efforts of the Health Office and Puskesmas to provide rewards for the performance of officers in recording and reporting of maternal and childh health program data, so that help make the KIA program a success.The implementation of the Maternal and Child Health program cannot be separated from recording and reporting as documentation and evalution of all activities that have been carried out